2005
DOI: 10.1097/01.yic.0000166405.49473.70
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic drugs and QT prolongation

Abstract: Antipsychotic drugs (AD) are effective and frequently prescribed to more females than males. AD may cause serious cardiovascular side-effects, including prolonged QT interval, eventually leading to torsades de pointes (TdP) and sudden death. Epidemiologic data and case-control studies indicate an increased rate of sudden death in psychiatric patients taking AD. This review summarizes current knowledge about the QT prolonging effects of AD and gives practical suggestions. Amisulpride, clozapine, flupenthixol, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(89 citation statements)
references
References 47 publications
1
87
0
1
Order By: Relevance
“…Many studies have reported the effect of antipsychotics on QTc prolongation (37,38), being the most common thioridazine (withdrawn from the Spanish market in 2005) and ziprasidone (39). The effect of aripiprazole on the QTc interval in electrocardiograms remains unclear.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Many studies have reported the effect of antipsychotics on QTc prolongation (37,38), being the most common thioridazine (withdrawn from the Spanish market in 2005) and ziprasidone (39). The effect of aripiprazole on the QTc interval in electrocardiograms remains unclear.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Use of fluoroquinolones, which have been a cause for concern to their risk for TdP,30 are not promoted as first line 29. Safety issues have also been raised for use of QTc‐prolonging anti‐psychotic medications 2, 31. Such drugs are frequently used in‐hospital inpatients as delirium can affect a fifth of acute medical admissions 32.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs share an ability to block the rapid component of the delayed rectifier K + current (IKr), resulting in a delayed repolarization of the cardiac action potential and prolongation of the QT interval, possibly leading to torsades de pointes [1]. Several epidemiological studies and case-control reports have shown that the rate of sudden death is increased in psychiatric patients taking antipsychotic drugs [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic drugs have been known to cause serious cardiovascular side-effects, including myocarditis, cardiomyopathy and abnormal cardiac rhythm [1]. These drugs share an ability to block the rapid component of the delayed rectifier K + current (IKr), resulting in a delayed repolarization of the cardiac action potential and prolongation of the QT interval, possibly leading to torsades de pointes [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation